Strategi Komunikasi Organisasi Dalam Meningkatkan Profesionalisme Bhabinkamtibmas Di Polres Mataram - Getas, I Wayan; Sukarta, Gede (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2025)
This research aims to examine and analyze Organizational Communication Strategies in Improving Bhabinkamtibmas Professionalism in Mataram Police. Interpretive qualitative research aims to analyze and examine in more depth the Organizational Communication Strategy in Improving the Professionalism of Bhabinkamtibmas in the Mataram Police. With the results of the research. 1). The communication strategies implemented by the Mataram Police in improving the professionalism of Bhabinkamtibmas are 1). Effective internal communication, through regular briefings, digital coordination groups, and periodic training 2). Improving communication skills with the community, with socialization, persuasive training, and conflict resolution simulation in carrying out their duties, 3). The use of digital media to accelerate coordination and support the transparency of police work, 4). Communication strategies in handling social conflicts, which prioritize a humanist approach and build synergy with community leaders, 5). The importance of building a structured and efficient communication strategy, 6). External Communication Approach to the Community through the "Friday Curhat" Program, 7). Humanist Approach through Bhabinkamtibmas Social Media. 2. The obstacles and challenges faced in the implementation of communication strategies to improve the professionalism of Bhabinkamtibmas in the Mataram Police are 1). Limited human resources, 2). Lack of Understanding and Awareness of Bhabinkamtibmas Understanding and Awareness, 3). Bhabinkamtibmas Organizational Culture, 4). Technology and infrastructure. 3. What affects the effectiveness of communication strategies in improving the professionalism of Bhabinkamtibmas in the Mataram Police are 1). Training and Capacity Development of Bhabinkamtibmas, 2). Utilization of Technology and Social Media Communication Platforms, 3). Building Partnerships and Collaborative Cooperation with Institutions, 4). Feedback System and Evaluation of the Role of Bhabinkamtibmas, 5). Improvement of Facilities and Infrastructure for the Provision of Communication Equipment.